2010
DOI: 10.1143/apex.4.013103
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Superconducting Ba(Fe1-xCox)2As2Thin Films on Technical Ion Beam Assisted Deposition MgO Substrates

Abstract: The biaxially textured growth of superconducting Co-doped BaFe2As2 (Ba-122) thin films has been realized on ion beam assisted deposition (IBAD) MgO coated conductor templates by employing an iron buffer architecture. The iron pnictide coated conductor showed a superconducting transition temperature of 21.5 K, which is slightly lower than that of Co-doped Ba-122 films on single crystalline MgO substrates. A self-field critical current density of over 10 5 A·cm −2 has already been achieved even at 8 K. The curre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 14 publications
4
78
4
Order By: Relevance
“…On the other hand, Si et al 232) reported high-J c 11 films on IBAD-MgO tapes. Their J c values on the order of 10 5 A/cm 2 are comparable to that of Ba122:Co reported by Iida et al 205) but lower than that (1.2-3.6 MA/cm 2 ) of Ba122:Co reported by Katase et al 206) It is noteworthy that J c of their 11 film still remains above 10 4 A/cm 2 in a high magnetic field of 25 T, reflecting the high upper critical magnetic field.…”
Section: )supporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, Si et al 232) reported high-J c 11 films on IBAD-MgO tapes. Their J c values on the order of 10 5 A/cm 2 are comparable to that of Ba122:Co reported by Iida et al 205) but lower than that (1.2-3.6 MA/cm 2 ) of Ba122:Co reported by Katase et al 206) It is noteworthy that J c of their 11 film still remains above 10 4 A/cm 2 in a high magnetic field of 25 T, reflecting the high upper critical magnetic field.…”
Section: )supporting
confidence: 86%
“…42(a)] show a sharp transition, indicating that granularity is not an issue (i.e., no weak-link behavior). Values of self-field J c of 3.6, 1.6, and 1.2 MA/cm 2 , which are higher than that reported by Iida et al, 205) were obtained for Á0 MgO ¼ 7:3, 6.1, and 5.5…”
Section: Wires and Tapescontrasting
confidence: 61%
“…By comparing with similar studies on Co-doped BaFe 2 As 2 coated conductors 6 , we point out the necessity of biaxial texture in oxypnictide wires and tapes for high J c .…”
Section: 13mentioning
confidence: 55%
“…These results suggest that the discovered iron based superconductors are exhibiting weak link grain boundary behavior similar to high-T c cuprate superconductors. An effective method to overcome the weak link problem is to engineering textured grains in iron based superconductors to minimize deterioration of the critical current density across high-angle grain boundaries.Recently Co-doped Ba122 coated conductors have been grown by several groups utilizing the existing YBCO coated conductor technology and have reached a self-field J c over 1 MA/cm 2 [21][22][23]. However, the technology has the shortcoming of low production rate, complexity and high equipment cost.…”
mentioning
confidence: 99%